Makers and takers the rise of finance and the fall of American business - Foroohar, Rana (New York Crown Business, 2016)
"Eight years on from the biggest market meltdown since the Great Depression, the key lessons of the crisis of 2008 still remain unlearned--and our financial system is just as vulnerable as ever. Many of us know that our government failed to fix the banking system after the subprime mortgage crisis. But what few of us realize is how the misguided financial practices and philosophies that nearly toppled the global financial system have come to infiltrate ALL American businesses, putting us on a collision course for another cataclysmic meltdown. Drawing on in-depth reporting and exclusive interviews at the highest rungs of Wall Street and Washington, Time assistant managing editor and economic columnist Rana Foroohar shows how the "financialization of America" - the trend by which finance and its way of thinking have come to reign supreme - is perpetuating Wall Street's reign over Main Street, widening the gap between rich and poor, and threatening the future of the American Dream. Policy makers get caught up in the details of regulating "Too Big To Fail" banks, but the problems in our market system go much broader and deeper than that. Consider that: · Thanks to 40 years of policy changes and bad decisions, only about 15 % of all the money in our market system actually ends up in the real economy - the rest stays within the closed loop of finance itself. · The financial sector takes a quarter of all corporate profits in this country while creating only 4 % of American jobs. · The tax code continues to favor debt over equity, making it easier for companies to hoard cash overseas rather than reinvest it on our shores. · Our biggest and most profitable corporations are investing more money in stock buybacks than in research and innovation. · And, still, the majority of the financial regulations promised after the 2008 meltdown have yet come to pass, thanks to cozy relationship between our lawmakers and the country's wealthiest financiers. Exploring these forces, which have have led American businesses to favor balancing-sheet engineering over the actual kind and the pursuit of short-term corporate profits over job creation, Foroohar shows how financialization has so gravely harmed our society, and why reversing this trend is of grave importance to us all. Through colorful stories of both "Takers" and "Makers," she'll reveal how we change the system for a better and more sustainable shared economic future"-- Provided by publisher.
"Award-winning business journalist Rana Foroohar shows how the shortsighted and misguided financial practices that nearly toppled the global economy in 2008 have come to infiltrate all corners of American business--putting us on a dangerous collision course to another economic meltdown that will make 2008 look like a mere blip in the business cycle"-- Provided by publisher.
Includes bibliographical references (pages 331-375) and index.
Keywords: Financial crises -- United States -- History -- 21st century; Finance -- Government policy -- United States -- History -- 21st century; Business enterprises -- United States -- History -- 21st century